ETIKA MENCARI ILMU KAJIAN KITAB WASHOYAA AL ABAA’ LIL ABNAA’ KARYA MUHAMMAD SYAKIR PERSPEKTIF PENDIDIKAN ISLAM - Nurul Lailiyah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2019)
Ethics seeking knowledge is about human behavior in the form of attitudes, actions or other originating from the human mindset that aims to know something in accordance with the actual situation with certain knowledge. In the book of washoyaa about ethics seeking knowledge has a clearer and more detailed thought. Starting from how to behave well towards educators and fellow friends in seeking knowledge. Ethics Looking for Knowledge in the Book of Washoyaa Al Abaa 'Lil Abnaa'Being Serious includes Studying earnestly and passionately, Using the best time,in reading and understanding lessons that have been discussed by the teacher or not yet discussed, No doubt- feel free to ask questions and discuss with friends, do not move to other problems, before completing the first problem and can understand it well, obedient and submissive to the teacher, do not fight with friends, do not talk alone with friends, be serious in listening to information from teacher and not empty minded (polite), polite to the teacher, remind each other with friends, Tawadlu (humble) and good morals, away from the nature of takabbur and despicable morals, Looking for the pleasure of teachers and ask for prayer to teachers, Munajat ( dialogue) and tawakal (surrender) to Allah.